Kebijakan Strategis Dalam Mengoptimalisasi Pendapatan Pajak Hotel dan Restoran - Hasanuddin Hasanuddin; Muhammad Anas; Mulyana Machmud (Al-Buhuts, 2022)
The purpose of this study is to formulate a strategic policy for hotel and restaurant tax revenues in Soppeng Regency, using an Internal Factor Evaluation (IFE) matrix and an External Factor Evaluation (EFE) matrix with a SWOT analysis approach. This type of research is a survey method and a descriptive approach with sampling based on proportional random sampling technique with a total sample of 16 hotels and 100 restaurants. Collecting data through field research, direct observation at the research site with the aim of obtaining primary data in the form of questionnaire data and important information as additional data accuracy. The results of the study indicate that the promotion and optimization of the management of tourist objects in encouraging an increase in domestic and foreign tourist visits, improvement of urban structure and road infrastructure development, application of information technology-based tax payment systems integrated with banking, increased participation of taxpayers in socialization of utilization taxes and the importance of paying taxes, improvement of the taxpayer database based on the classification of business fields